Northern Impulse in Creative Development of Andrei Bely - N. G. Sharapenkova (Научный диалог, 2025)
The relevance of this study is underscored by the scholarly significance of the issue of Russian-Scandinavian connections, particularly at the turn of the 19th to 20th centuries. This article examines the early works of one of the most prominent figures of Russian symbolism, Andrei Bely, within the context of the cultural dialogue between Russia and Scandinavia. Utilizing recently introduced autobiographical material, which is crucial for a comprehensive analysis of Bely’s writings, the research provides a concise overview of approaches to symphonies, with a focus on the “Northern Symphony (First Heroic).” Through an exploration of Bely’s autobiographical and epistolary heritage, the study identifies his reception of the music of Edvard Grieg and the dramas of Henrik Ibsen, analyzing images inspired by themes of the North, Scandinavian folklore, and mythology. The motifs of the “Northern Symphony (First Heroic)” — such as Eternity, Dawn, and Timelessness — are delineated. The findings suggest that the artistic space of the “Northern Symphony” is presented as a “space of consciousness” for the narrator. The research reveals characteristics such as Bely’s orientation towards the structure of musical composition, expressive techniques, and the incorporation of rhythm into prose. It is argued that these elements later manifest in Bely’s subsequent works (“Petersburg,” 1913; “Moscow,” 1924- 1932).